2017
DOI: 10.1002/joc.5116
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic classification of the summer season for the Levant using an ‘environment to climate’ approach

Abstract: The Levant region is dominated in the summer by the persistent Persian Trough. Thus, the current synoptic classifications lack the ability to reflect inter‐diurnal variations in the local weather conditions. This study aims to overcome this weakness and has two objectives: to develop operative prediction equations for the local weather conditions based on synoptic‐scale data, and to propose a new synoptic classification, based on the environment to climate approach, to better reflect the local climatic stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…This period is entitled hereafter, the 'synoptic summer'. The classification of the summer days is based on the climatic stress index (CSI), developed by Saaroni et al (2017). This index is calculated based on a prediction equation (i.e., a regression model) that combines the normalized and standardized national heat stress and the height of the persistent marine inversion.…”
Section: Methodsmentioning
confidence: 99%
“…This period is entitled hereafter, the 'synoptic summer'. The classification of the summer days is based on the climatic stress index (CSI), developed by Saaroni et al (2017). This index is calculated based on a prediction equation (i.e., a regression model) that combines the normalized and standardized national heat stress and the height of the persistent marine inversion.…”
Section: Methodsmentioning
confidence: 99%
“…The CSI is comprised of the national heat stress index, 125 used operationally by the Israel Meteorological Service, and the boundary layer height, which is a major factor influencing the summer weather conditions over the Eastern Mediterranean (Ziv et al, 2004). Saaroni et al (2017)…”
Section: Heat Wave Definition According To the Climatic Stress Index mentioning
confidence: 99%
“…Trough occurs on more than nine out of eleven days. For additional details on the computation of the CSI index and its evaluation, the reader is referred to Saaroni et al (2017).…”
Section: Heat Wave Definition According To the Climatic Stress Index mentioning
confidence: 99%
“…Still, episodes when the temperature drops to below normal values do occur, some of which are accompanied by summer rains (Saaroni and Ziv, 2000). Saaroni et al (2017) detected weaknesses in the ability of earlier synoptic classifications (Alpert et al, 2004a;Dayan et al, 2012) to describe local weather conditions during the eastern Mediterranean summer season. The authors proposed a "climatic stress index" (CSI), which is a combination of the national heat stress index, used operationally by the Israeli Meteorological Service, and the height of the marine inversion base height (see Sect.…”
mentioning
confidence: 99%
“…In this framework, the temperature of an air parcel increases by (i) adiabatic warming related to descent and (ii) diabatic heating including latent and sensible heat fluxes, shortwave radiation and long-wave radiation (Holton, 2004). Recent studies have revealed that extreme temperatures during heat waves are most often a combination of adiabatic warming related to descent and diabatic heating near the surface (e.g., Black et al, 2004;Bieli et al, 2015;Santos et al, 2015;Quinting and Reeder, 2017;Zschenderlein et al, 2019). The adiabatic warming is typically associated with upper-level ridges, which promote subsidence.…”
mentioning
confidence: 99%